Low frequency radio counterparts of HESS J1731−347 a.k.a SNR G353.6−0.7. Issue Volume 12:Issue S331(2017) (17th October 2017) - Nayana, A. J.; Chandra, Poonam
Abstract: HESS J1731−347 a.k.a. SNR G353.6−0.7 is one of the five known very high energy (VHE, Energy > 0.1 TeV) shell-type supernova remnants. We carried out Giant Metrewave Radio Telescope (GMRT) observations of this TeV SNR in 1390, 610 and 325 MHz bands. We detected the 325 and 610 MHz radio counterparts of the SNR G353.6−0.7 (Nayana et al. 2017). We also determined the spectral indices of individual filaments and our values are consistent with the non-thermal radio emission. We compared the radio morphology with that of VHE emission. The peak in radio emission corresponds to the faintest feature in the VHE emission. We explain this anti-correlated emission in a possible leptonic origin of the VHE γ-rays.